Persistensi Laba dan Suku Bunga terhadap Penilaian Ekuitas - Salijah Narwawan; Fajar Rina Sejati; Sahrul Ponto (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This study aims to test and obtain empirical evidence regarding the effect of profit persistence and interest rates on equity valuation. This study uses a sample of Property and Real Estate Sector Companies listed on the Indonesia Stock Exchange in 2018-2022. The research method used in this study is the purposive sampling method using SPSS 21 for data analysis. This type of company is quantitative with a population of 92 companies and 23 companies that are used as research samples with 5 (five) years of observation, so that the total research sample is 115 samples. The analysis technique used is multiple regression. The results of this study show that profit persistence has no effect on equity valuation. Meanwhile, interest rates have a significant positive effect on equity valuation.